Strategies for Facilitating Success of First Nations Students - Hampton, Mary; Roy, Joan (Canadian Journal of Higher Education, 2002)
This research suggests guidelines for college instructors which could help them facilitate success of First Nations students based on written narratives and data from four focus groups: (1) two groups of First Nations students; (2) two Faculty of Arts focus groups consisting of professors from the Saskatchewan Indian Federated College and the University of Regina who were identified as effective teachers of First Nations students. Data analysis revealed five themes that identify strategies that individual faculty members, as well as university program groups can use to create more positive learning environments for First Nations students: (1 ) enhancing the professor-student relationship; (2) including relevant First Nations content in curriculum; (3) using flexible teaching methods; (4) adopting a more culturally-appropriate teaching style; and (5) gaining an understand- ing of the unique life of a postsecondary First Nations student.